The Role Of The Village Funds And The Impact Of Village Financial System On Village Development Performance In Central Sulawesi (E-Jurnal Akuntansi, 2026)
Local governments play a crucial role in optimizing financial resources for development in rural areas by ensuring that these funds are used efficiently to meet community needs.  The purpose of this study is to examine how much the village financial system and money influence village development performance, specifically in terms of reaching the Village Development Index (IDM).  Regression analysis and a quantitative methodology were employed in the study, which included a sample of 1,821 observations and secondary data from Central Sulawesi village administrations in 2021.  Based on three important components the Social Resilience Index (IKS), the Economic Resilience Index (IKE), and the Environmental Resilience Index (IKL) the findings demonstrate that village finances and the village financial system have an impact on development performance.  However, the influence of village money on development performance is lessened when the village financial system serves as a moderator. This study provides important insights for stakeholders, including the government and non-governmental organizations, in developing more effective and responsive village development policies that address the needs of rural communities. The implication of this research is that village governments need to optimize village funds and the village financial system to support financial achievements, improve infrastructure, facilities, and the economy, so that village development performance can be more optimal and sustainable.
Keywords: Village Funds; Village Financial System; Village Development Performance